(untitled) (Journal of Multidisciplinary Sciences and Innovations, 2025)
The article analyzes theoretically and experimentally the thermodynamic properties of crystalline and amorphous polymers, such as heat capacity, thermal conductivity and thermal expansion. The application of the Debye and Tarasov models to the heat capacity of polymers, especially their behavior at low temperatures, is considered. The influence of the degree of crystallization on thermal conductivity is also illustrated by the example of polymers such as polyethylene. The influence of low-frequency optical vibrations arising in amorphous polymers on heat capacity is emphasized. The article also provides theoretical formulas for determining the expansion coefficients of polymers and explains their physical meaning.